Implementasi Self Assessment Untuk Meningkatkan Keterampilan Proses Sains Dan Kemampuan Kognitif Tingkat Tinggi Melalui Pembelajaran Berbasis Riset - Linawati Kuswanda; Sulistyono Sulistyono; Anna Fitri Hindriana (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2019)
This study aims to improve the KPS and students' high cognitive abilities after the implementation of self assessment through research-based learning. The research method used is mixed methods with Sequential Exploratory design. The population of this research is the students of class XI one of the vocational competence of nursing skills in Cirebon Regency. The research sample consisted of two classes determined by purposive random sampling technique, namely control class amounted to 27 people and 27 experimental class. The results showed that the average of self-assessment of the experimental class students is 81% with the superior category. The result of observation of experimental class KPS based on teacher observation is 88% with superior category and observation result of control class KPS is 77% with competent category. Thus, KPS increases after the implementation of self assessment. The data of research result of high level cognitive ability obtained by giving cognitive test at cognitive level of C3 until C6 growth and plant growth material in the form of pre test and post test. The collected data were analyzed by using descriptive statistics and comparative inferential statistics 2 paired sample groups. The result of descriptive analysis shows that the average value of pre test result of experiment class is 45,74 and post test result is 82,96, N-gain 0,70 with high category. The mean value of pre test result of control class 54,72 and post test result is 67,22, N-gain 0,30 with low category. KKM Biology lesson in class XI is 70, this shows the average post test experimental grade above KKM and control class is still below KKM. The result of t test dependent on pre test score and post test of high cognitive ability obtained by significance value 0,00 (sig <0,05) hence Ho refused and Ha accepted. This proves that Self Assessment can improve students' high cognitive abilities. Thus it can be concluded that the implementation of Self Assessment can improve the KPS and students' high cognitive abilities on the material growth and development of plants through research-based learningKeywords: Self assessment; Science process skills; High cognitive abilities; Research-based learning